(3edNU JGQjN GdESdGe ddPgHjs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , J (B833 (3g` s; (3GdPgHj,J (B748 (3g` s ((3eDjO RGOg YHO GdQMef Hf Ydi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdMhGOK hGdhajGJ CYXe YHQI ddEfSGf s
(3BNQgG (B:s
(3hgPG BNQ eG dNUJg ef JGQjN GdPgHj haQZJ efg ai jhe GdLeYI QGHY TgQ QLH (B798 (3HeOjfI CfWGcjI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
Keywords: (3GdJGQjNs